EFEKTIVITAS KETERAMPILAN KOMUNIKASI KONSELOR TERHADAP KETERBUKAAN DIRI SISWA DI SMA NEGERI 3 PAREPARE - Aswar Anas; Iskandar Iskandar; Zulfah Zulfah (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2018)
This study examines the effectiveness of counselor communication on the self-disclosure of students in SMA Negeri 3 Parepare. Counselors in high schools get a clear role and position or place, where counselors as a component of student support services (student support services) to help the development of personal, social, career, and academic aspects of students through guidance and counseling programs to students in plan (individual student planning), responsive service delivery and system development (system support). Therefore, counselors are highly required to have effective communication skills to support counseling, so counseling communication skills can make students open themselves. This type of research is descriptive qualitative using observation, interview, and documentation methods. The subject in this study was the BK teacher of SMA Negeri 3 Parepare as the school counselor using data analysis techniques namely interpretation data analysis techniques and triangulation analysis techniques. The results of this study indicate that the stages of counseling can be seen based on the stages of effective communication conducted by counselors, including; 1) Fact finding, 2) Planning, 3) Communicating, 4) Evaluating. The communication skills applied by counselors in the implementation of counseling are (attending), empathy, summarizing, asking, and honesty. By using the communication model, in this study found that the counselor's communication achieved students' self-disclosure as evidenced by giving their trust to the counselor, expressing honest statements in the counseling process, and students feeling relieved after the counseling. Based on some of the results obtained by researchers, the communication skills conducted by counselors to achieve students' self-disclosure are effective.